Usos de la conjunción pero en el habla lojana - Romero Ganazhapa, Mercedes Mariela (2025)
The objective of this research is to analyze the uses of the conjunction pero in the speakers of the Loja region. To achieve this purpose, specific objectives were set to identify the semantic and pragmatic nuances associated with this conjunction, as well as to describe its uses from a sociolinguistic perspective in the population of Loja. Methodologically, we used a corpus compiled by a group of researchers from the National University of Loja, composed of 111 interviews with 66 female and 45 male informants in the province of Loja. The most relevant results indicate that the six most frequent uses of the conjunction pero in the region are the following: three of semantic status -modifying adversative pero, justifying adversative pero and rectifying adversative pero- and three of pragmatic status -counter-argumentative pero with the use of sí pero; pero bueno: resigned acceptance; and cases of the expressions sí, pero pero no. The most relevant results indicate that the modifying adversative pero allows multiple additional features to be added. Lojano speakers with the adversative pero of justification usually complement the adversative sentence with the causal conjunction porque in order to specify a cause or reason. The significant presence of the rectifying adversative pero demonstrates its currency in Lojano speech. The uses of pero contra-argumentative with the use of sí pero and the case of the expressions of sí, pero no, always require a previous intervention or a question from another interlocutor for these uses to occur. In the case of pero bueno, its predominant function in Lojano speech is to express resigned acceptance